Assessment of mandibular ramus for sex determination: Retrospective study - Alime Okkesim; Türkan Sezen Erhamza (Elsevier, 2020)
Background: The determination of sex is as a keystone in the identification. The skull is considered the second-best mark of gender determination. However in cases where a complete dry skull is not found, the mandible may play an important role in gender estimation as it is the most dimorphic, largest, and strongest bone of the skull. Studies showed cone beam computed tomography (CBCT) found better than traditional methods. The using of CBCT device can obtain undistorted and good-quality 3D images with a low radiation dose.In this study, it was purposed to measure the morphometric parameters of the 3D mandible models in the Central Anatolian Turkish population and to evaluate the effectiveness of measurements in gender determination. Method: The study was consisted of 70 individuals (35 males, 35 females; mean age 24,69 ± 2,85 years). Linear parameters were measured in mm using the mouse-driven method. The measurements were recorded from the both of right and left side. Acquired measurements between groups were evaluated with Student t-test. Results: In the present study five different parameters of mandible were measured and mean values were determined. It was found that all variable of mandibular ramus on CBCT models showed a statistically significant difference among the sex (p < 0.05). Conclusions: Mandibular ramus measurements can be useful tool for sex determination. These results propose that the mandible describes sexual dimorphism in the modern adult Central Anatolian Turkish population. However further studies with larger populations are needed to reveal this relation.